Proceedings of the URECA@NTU 2017-2018 - Students of URECA Programme (2019)
Proceedings of the URECA@NTU 2017-18 is a compilation of selected URECA and Interdisciplinary-URECA and Final Year Project-URECA research papers, submitted by the URECA students of 2017-18, and under the supervision of their respective URECA supervising professors.